Environmental Factors and Semiarid Plants Species on Eroded Marly Soils in Southwest Anatolia (Eskişehir/Türkiye) - Nejat Celik; Neslihan Balpınar; Münevver Arslan; Mesrur Ümit Bingöl (Journal of Agricultural Sciences)
The natural regeneration of vegetation in areas of marly soils is restricted due to drought and soil erosion. For the ecological restoration of eroded areas, the selection of suitable plant species is critical. The aim of this study is to assess specific plant species and their ecological characteristics for their ability to thrive under drought in eroded areas with marly soil. The study was conducted on 36 sampling locations in the marly areas of Eskisehir-Bozan, Türkiye, during the most drought-prone months, August and September, in 2011 and 2012. Vegetation sampling was conducted according to the Braun-Blanquet method. Fifteen plant taxa with the highest coverage and frequency were identified. Relationships between plant species and environmental factors were determined using Spearman’s correlation analysis. According to the results of numerical analysis, there were correlations between ecological parameters including nitrogen, phosphorus, organic matter, lime, slope, altitude and plant taxa. The resistance rate of fifteen plant taxa in marly areas is quite high even in the driest months. These plant taxa, possessing properties essential for soil protection, may be used for revegetation practices of marly areas exposed to soil erosion. This study’s findings will provide useful guidance for vegetation programs.